2015
DOI: 10.1007/s12274-015-0828-5
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the balance between intracellular glutathione and polyethylene glycol for successful release of small interfering RNA from gold nanoparticles

Abstract: The therapeutic promise of small interfering RNAs (siRNAs) for specific gene silencing is dependent on the successful delivery of functional siRNAs to the cytoplasm. Their conjugation to an established delivery platform, such as gold nanoparticles, offers tremendous potential for treating diseases and advancing our understanding of cellular processes. Their success or failure is dependent on both the uptake of the nanoparticles into the cells and subsequent intracellular release of the functional siRNA. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…This was most notable with the osteo-committed MG63s, where a 5A-mediated reduction in C-Myc expression alongside an increase in runx2 and SMAD3 indicated that the cells were perhaps reducing proliferation to focus on enhancing commitment along the osteoblast lineage ( Fig 5A ). Also with the more primitive MSCs, BMPR-2 and BMP-R1A, which are co-involved in the very early cell signalling pathways for osteogenesis [ 22 ], transcript changes may suggest early stages of osteo-commitment ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was most notable with the osteo-committed MG63s, where a 5A-mediated reduction in C-Myc expression alongside an increase in runx2 and SMAD3 indicated that the cells were perhaps reducing proliferation to focus on enhancing commitment along the osteoblast lineage ( Fig 5A ). Also with the more primitive MSCs, BMPR-2 and BMP-R1A, which are co-involved in the very early cell signalling pathways for osteogenesis [ 22 ], transcript changes may suggest early stages of osteo-commitment ( Fig 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…RNAhybrid predicts the minimum free energy hybridization of two RNA sequences, allowing for miR target prediction. Hybridization is assessed by domain analysis with one sequence hybridized to the best fitting part of another [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold nanoparticles (AuNP) are biologically inert, easily synthesized, commercially available and highly stable composites [173,174]. Over the last decade, they have gained great popularity in the biomedical field.…”
Section: Assessing Rnai Delivery For Gbm Treatmentmentioning
confidence: 99%
“…29,[32][33][34] AuNPs are biologically inert, easily synthesized, commercially available, and highly stable composites. 35,36 They possess feasible characteristics that enable their application in diagnostics, imaging, and therapy. 16,32,36,37 The surface of AuNPs can enable multiple coupling with drugs, CNS-specific ligands, and oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%